Classifying Madness A Philosophical Examination of the Diagnostic and Statistical Manual of Mental Disorders - Cooper, Rachel; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Classifying Madness examines the conceptual foundations of the D.S.M., the main classification of mental disorders used by psychiatrists world-wide. It will be of interest to both mental health professionals and to philosophers interested in classification in science. The D.S.M. has become extremely controversial, and the possibility that there may be philosophical difficulties with it has become a commonplace in the mental health literature. Classifying Madness offers mental health professionals an opportunity to explore suspicions that there might be conceptual problems with the D.S.M. For philosophers, this book aims to contribute to debates in the philosophy of science concerning natural kinds, the theory-ladenness of classification, and the effect of sociological factors in science. These issues are normally approached via a consideration of the natural sciences and, as will be seen, approaching them via a consideration of psychiatry helps shed new light on old problems.
What is Mental Disorder? -- Are Mental Disorders Natural Kinds? -- The Problem of Theory-Ladenness -- The D.S.M. and Feedback in Applied Science.
Keywords: PHILOSOPHY (GENERAL).; MEDICINE -- PHILOSOPHY; SCIENCE -- PHILOSOPHY; SOCIAL SCIENCES -- PHILOSOPHY; MEDICINE; PHILOSOPHY; PHILOSOPHY OF MEDICINE; PHILOSOPHY OF SCIENCE; HISTORY OF MEDICINE; PHILOSOPHY OF THE SOCIAL SCIENCES